Scaling Constraints in Junior Tennis: The Influence of Net Height on Skilled Players' Match-Play Performance. Issue 1 (2nd January 2018) - Limpens, Vera; Buszard, Tim; Shoemaker, Emma; Savelsbergh, Geert J. P.; Reid, Machar
ABSTRACT: Purpose : The net height in tennis (0.91 m) is approximately 50% of a professional tennis player's height. Children are also expected to play with this net height, even though it is approximately 70% of the average 10-year-old's height. This study examined the immediate effect of lowering net height on the performance characteristics of skilled junior tennis players aged 10 years and younger.Method : Sixteen players were matched in 8 pairs of even tennis ability and same sex. Each pair played 25-min singles matches in 4 conditions that varied in net height (0.91 m, 0.78 m, 0.65 m, and 0.52 m). Match-play characteristics were analyzed via video replay.Results : Results showed that lowering the net height to 0.65 m and 0.52 m led to players adopting a more attacking style of play, as evidenced by a significant increase in the number of winners without a commensurate increase in errors and more shots struck inside the baseline. Lower nets also led to a greater percentage of successful first serves. The lowest net (0.52 m), however, reduced rally length significantly and therefore decreased hitting opportunities.Conclusion : These results offer support for equipment scaling to enhance match-play performance for skilled junior tennis players. We propose that current net height recommendations for junior tennis should be revised.